Implant? Prosthesis? Inclusion? Implante? Prótese? Inclusão? - César Augusto Arrunátegui Carvallo (Revista Brasileira de Cirurgia Plástica)
The author discusses the indiscriminate use of various terms to designate a single artifact and suggests the adoption of only one signifier. Although no publications deal specifically with the meaning of the terms "implant", "prosthesis" or "inclusion", apart from what is found in ordinary lexical and medical dictionaries, such terms are commonly and interchangeably used to designate a single artifact. According to the author, it is beneficial to select and utilize only the term that best conceptualizes the object designed for correcting lack of breast volume in specialty terminology. The use of a single term will facilitate scientific paper writing; therefore, the author proposes the use of the term "implant" to indicate the artifact placed inside the mammary gland. O autor discute o uso indiscriminado de vários termos para designar um único artefato e sugere a adoção de apenas um significante. Embora não se encontrem publicações que tratem especificamente do significado dos termos implante, prótese e inclusão, a não ser o que se encontra nos dicionários léxicos e médicos comuns, esses termos têm sido usados rotineiramente para designar um único artefato. O autor considera ser possível incluir na nomenclatura da especialidade o termo que melhor conceitue o referido objeto destinado à correção da falta de volume mamário. O uso de um único termo facilitaria a redação de trabalhos científicos, e, por esse motivo, o autor propõe o uso do termo implante para o artefato colocado dentro da glândula mamária.